Minimizing Time Complexity based on Parallel Processing using RNS for Audio (International Journal of Engineering and Computer Science, 2015)
In this paper, we propose a secure mechanism to transfer sensitive audio files over an unreliable network. In order to prevent the unauthorized access of data that can be collected at the time of data transmission, a secure approach is introduced Audio Cryptography with parallelism that may be some of the future solution for the above mentioned problem. The proposed approach uses the suitable technique such as the Pseudo Random Number Generation(PRNG) method with seed called as the Initial Vector (IV) as the parameter for generating random numbers and the Residual Number System for encryption. The audio file is in turn encrypted using the keys generated using the PRNG. The concept of Residual Number System (RNS) based on Chinese Remainder Theorem (CRT) for share creation is performed in parallel to maximize the resource utilization and make the process faster. These, audio shares are sent over the channel over the network to increase security. Theoretical analyses and experimental results show that, there is significant reduction in time consumption.